The Diagonal Problem for Higher-Order Recursion Schemes is Decidable - Clemente, Lorenzo; Parys, Paweł; Salvati, Sylvain; Walukiewicz, Igor (Proceedings of the 31st Annual ACM/IEEE Symposium on Logic in Computer Science, 2016)
A non-deterministic recursion scheme recognizes a language of finite trees. This very expressive model can simulate, among others, higher-order pushdown automata with collapse. We show decidability of the diagonal problem for schemes. This result has several interesting consequences. In particular, it gives an algorithm that computes the downward closure of languages of words recognized by schemes. In turn, this has immediate application to separability problems and reachability analysis of concurrent systems.